2013
DOI: 10.1007/s00418-013-1154-1
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal region of teneurin-1 co-localizes with the dystroglycan complex in adult mouse testes and regulates testicular size and testosterone production

Abstract: Testicular size is directly proportional to fertility potential and is dependent on the integration of developmental proteins, trophic factors, and sex steroids. The teneurins are transmembrane glycoproteins that function as signaling and cell adhesion molecules in the establishment and maintenance of the somatic gonad, gametogenesis, and basement membrane. Moreover, teneurins are thought to function redundantly to the extracellular matrix protein, dystroglycan. Encoded on the last exon of the teneurin genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
9
1
Order By: Relevance
“…5M-P). In these studies, however, a strong immunoreactive-TCAP signal on the plasma membrane in cell culture or at the basement membrane was not observed as previously established in mouse tissue (Chand et al, 2013a), because the epitope may have been obscured by the globular arrangement of the extracellular domain of the teneurins (Feng et al, 2002). Assuming this to be case, then we cannot discount the possibility that TCAP region of the C. intestinalis teneurin may act as a functional unit of teneurin by remaining tethered to it, in a similar manner to the notch signaling of serrate and delta ligands (Artavanis-Tsakonas et al, 1999;Hicks et al, 2002.…”
Section: Discussioncontrasting
confidence: 67%
“…5M-P). In these studies, however, a strong immunoreactive-TCAP signal on the plasma membrane in cell culture or at the basement membrane was not observed as previously established in mouse tissue (Chand et al, 2013a), because the epitope may have been obscured by the globular arrangement of the extracellular domain of the teneurins (Feng et al, 2002). Assuming this to be case, then we cannot discount the possibility that TCAP region of the C. intestinalis teneurin may act as a functional unit of teneurin by remaining tethered to it, in a similar manner to the notch signaling of serrate and delta ligands (Artavanis-Tsakonas et al, 1999;Hicks et al, 2002.…”
Section: Discussioncontrasting
confidence: 67%
“…These findings were partially resolved when TCAP-1 and teneurin-1 was investigated in the mouse testes. Here, the studies indicated a clear relationship of teneurin-1 with α-dystroglycan, and TCAP-1 with β-dystroglycan (Chand et al, 2014 ). However, in these studies, teneurin immunoreactivity was found at the cell membrane, whereas TCAP-1 immunoreactivity was typically found within the cytosol.…”
Section: Discovery and Structure Of Teneurins Tcap And Latrophilinsmentioning
confidence: 81%
“…As all Teneurin homologs possess an NHL domain (Figure 1 ), which can interact with integrins (Löer et al, 2008 ), this suggests that such a mechanism could be conserved across species. In mice, there is further interplay between Teneurin and Dystroglycan, as the C-terminal region of Teneurin-1 colocalizes with Dystroglycan (Chand et al, 2012 , 2014 ). In hippocampal cultures, application of this C-terminus regulates cytoskeletal organization (presumably through Dystroglycan) by increasing tubulin levels, actin polymerization, and filopodia length and rate of formation.…”
Section: How Do Teneurins Regulate Synaptic Organization?mentioning
confidence: 99%
“…Thus, Teneurin-1 is proposed to induce a signal beginning from Dystroglycan at the membrane and resulting in neurite elongation (Chand et al, 2012 ). In the testes, this interaction is conserved, as Teneurin-1 colocalizes with actin, regulating testosterone and testicular size (Chand et al, 2014 ). This conserved Teneurin-Dystroglycan interplay is thus poised to generally regulate the cytoskeleton.…”
Section: How Do Teneurins Regulate Synaptic Organization?mentioning
confidence: 99%